Multiparametric magnetic resonance imaging of endometrial polypoid lesions. - Lee, Youkyoung; Kim, Kyeong Ah; Song, Mi Jin; Park, Yang Shin; Lee, Jongmee; Choi, Jae Woong; Lee, Chang Hee (Abdominal Radiology, 2020)
Endometrial polypoid lesions encompass various conditions from physiologic changes to benign or malignant disease. Differentiating between the various causes of endometrial polypoid lesions remains difficult by transvaginal sonography. Magnetic resonance imaging (MRI) can provide valuable information regarding endometrial polypoid lesions in situations where it is difficult to obtain histologic samples. Multiparametric MRI including T2-weighted images, T1-weighted fat-saturation contrast-enhanced images, and diffusion-weighted images may be helpful for differentiating the various endometrial polypoid lesions and establishing specific diagnoses and appropriate treatment.